Escola e mobilidade social: um estudo sobre os egressos do SESI Vila Cisper - Repa, Marcos Henrique (2008)
This study aims to analyze the work done by SESI- Serviço Social da Indústria, as an educational institution concerned with professional development of its clients. The study also attempts to trace students' eventual contribution to social mobility, focusing on the individuals that studied at SESI, Vila Cisper. Interviews with the SESI - Vila Cisper's students, were used as the basis of the study. With the intent of determining the impact the course has made and is still making on students' lives; whether it be personal, social, professional or economical. This report draws on other sources to consummate its findings, such as: law decrees, documents related to professional formation, curriculum and pedagogical references from the SESI net and annual reports published by institutions of whom contribute considerable educational information via the internet. This accumulation of data aided in determining the pedagogical method used by SESI. It also assisted in ascertaining the availability of both human and material resources, how the students' knowledge progressed and the proposed goals in their education. And finally, the students' perception of the education they have received from SESI, in particular, with respect to, their eventual social mobility